Contextual Philosophy-Learning at the Faculty of Theology, Sanata Dharma University - Mulyatno, Carolus Borromeus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2018)
Philosophy learning is an integral part of the educational formation at the Faculty of Theology, Sanata Dharma University, Yogyakarta, Indonesia. It is integrated with theology and other sciences learning to shape the identity of the faculty and to contribute to the development of the community. The focus of this writing is to answer two questions: What are the basic considerations for choosing philosophy learning in this faculty? How can method choice be accounted for? By attending to the faculty’s history, the author finds that the basic considerations for choosing philosophy learning method at the faculty are the history faculty establishment and its academic vision. Historically, the existence of the faculty was related to the efforts of Semarang Archdiocese for priest preparation and local pastoral activist education. Philosophy learning is also related to the faculty’s academic vision that leads the students towards concrete involvement in building the church living in the context of pluralism in Indonesia. Inspired by Heidegger’s idea on phenomenological method, preferences to select existential analysis method for philosophy learning in the faculty contribute to the development of contextual theological reflection as well as to priest and pastoral worker preparation, by involving students in community life, dialogue, and living together in the society, based on the values from the local wisdom that are still relevant today.